The Changing Role of Chinese English-as-Foreign-Language Teachers in the Context of Curriculum Reform: Teachers’ Understanding of Their New Role - Lei, Man; Medwell, Jane (Frontiers in Psychology, 2022)
The New Curriculum Standards for teaching English introduced major changes in the culture of teaching and learning English in the Peoples Republic of China (PRC). Changes have been linked to changing goals for English instruction and a revision of Confucian values in schooling. In this paper, we argue that this English curriculum proposes a new role, with new demands, for English-as-foreign-language (EFL) teachers in the PRC. In order to implement the curriculum reform successfully, teachers involved in the reform are required to have a shared understanding of its nature, purposes and scope. However, little is known about to what extent EFL teachers understand and engage with their new roles. This study examines teachers’ understandings of the new curriculum and of the new, demanding role of teachers implied by the curriculum. This is a mixed methods study involving an analysis of the curriculum document, a survey (n=227) of EFL teachers and semi-structured interviews with a sample of teachers in the cohort (n=18). The findings suggest that many teachers know the content of the curriculum document, but expressed uncertainty about the implications of changes, uncertainty about what a shift to student-centered teaching and learning means and confusion about new professional development demands. The findings of this study have wider implications for EFL teachers, teacher educators, researchers and policy makers in the PRC and similar national contexts. This paper highlights that, from an international perspective, introducing new ideas and practices should consider teachers’ existing understanding and experiences of the curriculum as well as the way in which they understand the purposes of the changes, and should promote a shared understanding of policy intentions.